2015
DOI: 10.1038/nchem.2352
|View full text |Cite
|
Sign up to set email alerts
|

Stable, crystalline, porous, covalent organic frameworks as a platform for chiral organocatalysts

Abstract: The periodic layers and ordered nanochannels of covalent organic frameworks (COFs) make these materials viable open catalytic nanoreactors, but their low stability has precluded their practical implementation. Here we report the synthesis of a crystalline porous COF that is stable against water, strong acids and strong bases, and we demonstrate its utility as a material platform for structural design and functional development. We endowed a crystalline and porous imine-based COF with stability by incorporating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
1,064
2
22

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,375 publications
(1,121 citation statements)
references
References 42 publications
33
1,064
2
22
Order By: Relevance
“…By installing electron donating methoxy groups on the linear arene subunits a reduction of the imine bond polarization was achieved, a COF with enhanced stability and crystallinity in comparison to its nonmodified COF homologue was reported. [17] Introducing intramolecular hydrogen bonding was explored by Banerjee and co-workers as a method to stabilize iminebased COFs by induced planarization of the 2D COF sheets. [18] Adv.…”
Section: Long-range Ordermentioning
confidence: 99%
“…By installing electron donating methoxy groups on the linear arene subunits a reduction of the imine bond polarization was achieved, a COF with enhanced stability and crystallinity in comparison to its nonmodified COF homologue was reported. [17] Introducing intramolecular hydrogen bonding was explored by Banerjee and co-workers as a method to stabilize iminebased COFs by induced planarization of the 2D COF sheets. [18] Adv.…”
Section: Long-range Ordermentioning
confidence: 99%
“…[15][16][17][18] It has been revealed that the properties of polymer depend mainly on the polymer architecture as well as the intrinsic properties of synthons. For example, the polymers comprising of larger conjugated system is of benefit to the adsorption of H 2 19,20 as well as the fluorescent detection of Nitro-benzene derivatives, while the polymers with large N content usually exhibits promoted adsorption affinity toward CO 2 .…”
mentioning
confidence: 99%
“…[35] Furthermore, Jiang and coworkers have reported the metal-free heterogeneous organocatalysis of chiral COFs materials which display excellent activity, enantio-selectivity and recyclability. [36,37] Among chiral functional groups employed in asymmetric catalysts, so-called "privileged" chiral ligands such as 1-(2-hydroxynaphthalen-1-yl)naphthalen-2-ol (BINOL), 2,2'-bis(diphenylphosphino)-1,1'-binaphthalene (BINAP), salen, bisoxazoline and TADDOLate, have been proven to be highly efficient to a wide range of different reactions.…”
Section: Introductionmentioning
confidence: 99%